IGF-1 mediates exercise-induced phospholipid alteration in the murine skin tissues - Jiang, Yu; Ma, Haitian; Su, Xiaoyu; Chen, Jie; Xu, Jianteng; Standard, Joseph; Lin, Dingbo; Wang, Weiqun (My University, 2012)
We previously demonstrated that exercise with an iso-caloric diet significantly reduced body weight and skin carcinogenesis in correspondence with lower plasma IGF-1 levels and IGF-1-dependent phospholipid signaling. This study was thus designed to test the hypothesis that IGF-1 reduction plays a causal role in exercise-induced phospholipid changes. SENCAR mice were randomly assigned to one of the following three groups for 12 weeks: ad libitum-fed sedentary control, exercise but pair-fed the amount of the control (PE), and PE with IGF-1 injection (PE+IGF-1). Treadmill exercise was conducted at 13.4 m/min for 90 min/d, 5 d/week. In the last two weeks IGF1 was i.p. injected (10 μg/g B.W.) twice per week. Both body weight and plasma IGF-1 levels were significantly reduced in PE mice when compared with the control. IGF-1 injection did not affect body weight, or the plasma levels of IGF-1 at the end of the experiment due to a rapid degradation with a half-life of 3.4 hrs. Of the 338 phospholipid species detected in the skin tissues by electron spray ionization tandem mass spectrometry, 21 were significantly changed in PE mice compared to control. Fourteen of the altered 21 species in PE mice were reversed by IGF-1 injection, including the most abundant phosphatidylinositol (PI) 38:4, a substrate for lipid PI3K signaling. Western Blot Analysis further showed the reduced PI3K, but not IGF-1R, in PE mice was also reversed by IGF-1 restoration. Overall, these data provided evidence that exercise-induced reduction of IGF-1 is required in mediating the alteration of phospholipid profile and PI-related PI3K signaling.
Keywords: Weight control; Exercise; IGF-1; Phospholipids; Mice